The Challenge to Create Bangkok Smart Destination Image and Loyalty - Chompucum, Pramtip (KKBS Journal of Business Administration and Accountancy, 2018)
This paper aims to take advantage from the development of Smart Cities by conceptualising framework for Smart Tourism Destinations through exploring tourism applications in destination and addressing both opportunities and challenges to create Bangkok Smart destination image and loyalty